All-Weather 3D Self-Folding Fabric for Adaptive Personal Thermoregulation - Zhang, Xiaohui; Gu, Yuheng; Chao, Xujiang; Wang, Zhaokun; Wu, Shitong; Xu, Jinhao; Li, Ziqi; Pan, Mengjiao; Shou, Dahua (Nano-Micro Letters, 2025)
In the era of global climate change, personal thermoregulation has become critical to addressing the growing demands for thermoadaptability, comfort, health, and work efficiency in dynamic environments. Here, we introduce an innovative three-dimensional (3D) self-folding knitted fabric that achieves dual thermal regulation modes through architectural reconfiguration. In the warming mode, the fabric maintains its natural 3D structure, trapping still air with extremely low thermal conductivity to provide high thermal resistance (0.06 m2 K W−1), effectively minimizing heat loss. In the cooling mode, the fabric transitions to a 2D flat state via stretching, with titanium dioxide (TiO2) and polydimethylsiloxane (PDMS) coatings that enhance solar reflectivity (89.5%) and infrared emissivity (93.5%), achieving a cooling effect of 4.3 °C under sunlight. The fabric demonstrates exceptional durability and washability, enduring over 1000 folding cycles, and is manufactured using scalable and cost-effective knitting techniques. Beyond thermoregulation, it exhibits excellent breathability, sweat management, and flexibility, ensuring wear comfort and tactile feel under diverse conditions. This study presents an innovative solution for next-generation adaptive textiles, addressing the limitations of static thermal fabrics and advancing personal thermal management with wide applications for wearable technology, extreme environments, and sustainable fashion. Highlights: 1 An innovative 3D self-folding fabric was fabricated by knitting technology to achieve dual thermoregulation modes through architectural reconfiguration between 3D and 2D states. 2 In the warming mode, the fabric retains its natural 3D structure, providing high thermal resistance (0.06 m2 K W⁻1) by trapping still air. In the cooling mode, it transitions to a 2D flat state with coatings of thermal radiative management materials, achieving a cooling effect of 4.3 °C under sunlight by enhancing solar reflectivity and infrared emissivity, while reducing thermal resistance. 3 The fabric demonstrates exceptional durability and washability, enduring over 1000 folding cycles, and is manufactured using scalable and cost-effective knitting techniques.